Performance assessment of the stand-alone diesel power plant at San, Mali - Dembele, Pierre (2011)
A Thesis presented to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the Requirements for the Degree of Master of Science in Mechanical Engineering